Self, world, and art: metaphysical topics in Kant and Hegel - Emundts, Dina (De Gruyter, 2013)
Biographical note: Dina Emundts, University ofKonstanz.
Description based upon print version of record
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Kant, Immanuel -- 1724-1804; Konferenzschrift -- 2011 -- Berlin; Ästhetik; Kant, Immanuel; Metaphysik; Hegel, Georg Wilhelm Friedrich